Learning Management for Advancing SDG 4 through a Deep Learning Approach: A Multi-Site Case Study in Indonesian Junior High Schools - Aris Setiawan; Yatim Riyanto; Nunuk Hariyati (Journal of Current Studies in SDGs, 2026)
Objective: To describe, analyze, and construct propositions for a conceptual model of learning management through a deep learning approach at SMP Negeri 1 Gedangan and SMP Negeri 4 Sidoarjo. Method: The research employed a descriptive qualitative design using a multi-site case study approach. Data were collected through in-depth interviews, direct observation, and document analysis. The data were then analyzed through single-site and cross-site analysis to identify patterns, similarities, and conceptual findings from both research sites. Results: The findings show that the implementation of learning management through a deep learning approach requires principals to move beyond administrative and managerial functions toward a stronger role as instructional leaders. Principals facilitate teacher professional development through coaching, mentoring, and supportive clinical discussions. They also play a transformational role in translating curriculum vision into classroom practices based on mindful, meaningful, and joyful learning. Effective implementation is supported by teacher capacity building, principal managerial competence, curriculum integration, infrastructure optimization, digital technology utilization, and stakeholder collaboration. Novelty: Offering a conceptual model of learning management that integrates instructional leadership, teacher professional development, curriculum transformation, digital learning support, and stakeholder collaboration as strategic elements in implementing deep learning in junior high schools for SDG 4.